Corrupción y responsabilidad penal/administrativa de los partidos políticos - Tasayco, Gilberto Félix (2024)
This article analyzes the relationship between corruption and criminal-administrative responsibility of political parties. It is verified whether the phrase ‘political parties, private law entities should be interpreted as valid, to then determine if there is legislative provision regarding the criminal/administrative liability of political parties or if, in the absence of provision, the express incorporation in Law 30424. In addition, the possibility of including crimes against democratic participation –with emphasis on the crime of prohibited financing of political organizations– in Law 30424 is analyzed. Finally, we proceed to determine whether the system of sanctioning measures applicable to political organizations modified by Law 32054, must be regulated in the same terms as a company.